THE EFFECT OF IMPLEMENTING A COOPERATIVE LEARNING MODEL OF GROUP INVESTIGATION (GI) TYPE ON STUDENT LEARNING OUTCOMES ON ECOSYSTEM MATERIALS IN CLASS XA OF STATE MIDDLE SCHOOL 2 SINTANG - Marzuki, Marzuki (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study analyzed the effect of implementing the group investigation (gi) cooperative learning model on student learning outcomes on ecosystem material in class XA of SMA Negeri 2 Sintang. The researcher used a qualitative method to conduct the study. Thirty-four student samples from Class X A were taken using purposive sampling. The learning model implementation was going well and proven from the observation sheet; 84.62% of teachers and 88.89% of students were in the "excellent" category. The result of the normality test for pre-test data with the Chi-Square count table value is X2 count < X2 table or 6.93 < 11.070. Then, the post-test result is normal with the value X2 count < X2 table or 2.99 < 11.070. The pre-test homogeneity test obtained Fcount data at 2.5 ≤ Ftable 2.34. In the post-test homogeneity test, the data obtained was Fcount 1.6 ≤ Ftable 2.34, so the variances were homogeneous. In hypothesis testing, the data obtained was Tcount 9.35 > Ftable 2.34. Then H0 was rejected, meaning the group investigation cooperative learning model influenced student learning outcomes. The application of the Group Investigation (GI) type cooperative learning model to ecosystem material affects students' understanding and learning outcomes with a significant effect size (d) 1.64 (big criterion) because it is almost close to 2.0.